Educating on Mobile Computing and Security Practices - Yusfrizal Yusfrizal; Heri Gunawan; Yahya Tanjung (Yayasan Sinergi Multidimensi Kreatif, 2024)
With the increasing popularity of mobile devices, it has become essential to educate college and university students about mobile computing and security. This paper introduces eight course modules on mobile computing and security that we designed to integrate seamlessly into a computer science curriculum. These modules were showcased during a faculty workshop, where feedback was gathered through survey questionnaires and participants' reflective narratives. The evaluation results from the workshop are analyzed and discussed in this paper. These modules are adaptable for educators teaching mobile application development, cyber security, or other related subjects.